LONG-TERM FORECASTING THE DEVELOPMENT OF RELATIONS BETWEEN LOCAL HUMAN CIVILIZATIONS: CONCLUSIONS AND PROPOSALS - A. I. Podberezkin (Vestnik MGIMO-Universiteta)
The article is the form of scientific report on the results of three year long project on methodology of long term forecasting the development of the system of international relations. The methodology is based on the following assumptions: input information is accurate and complete; international relations constitute a system, scenarios for different levels of international relations development are hierarchically interdependent; the speed of development is different on various levels of international relations; various national capabilities affect the development; elites affect international relations; civil society affect international relations. Based on this assumption the author builds the most probable scenario of intercivilizational relations which is military coercive interaction. The role of soft power will increase its share in the toolkit of the confrontational politics. To win in this confrontation it is necessary to review the current practices of strategic forecasting and planning and to rebuild the entire military organization of the Russian army. The principal condition for the victory is development of national human capital, as well as the formation of the national ideology.